Microextraction experimental and forcefield theoretical modelling study on exploring a silica-enriched oil palm frond biomass for the determination of polycyclic aromatic hydrocarbons in Psidium guajava - Zainal Abidin, Nur Husna; Wan Ibrahim, Wan Nazihah; Raharjo, Yanuardi; Rashidi Nodeh, Hamed; Abdul Wahab, Roswanira; Yaakob, Muhamad Kamil; Yahaya, Noorfatimah; Kamaruzaman, Sazlinda; Mat Hadzir, Nursyamsyila; Mohamad Hanapi, Nor Suhaila (Elsevier Inc., 2024)
In this study, a dispersive micro-solid phase extraction (D-µ-SPE) based on oil palm frond-based silica (OPF-SiO2) sorbent was investigated for the determination of four polycyclic aromatic hydrocarbons (PAHs) in Psidium guajava integrated with high-performance liquid chromatography (HPLC-DAD). The physicochemical characterization of the acid-treated and thermally extracted OPF-SiO2 by FTIR showed peaks at 806 cm−1 and 446 cm−1 allotted to siloxane stretching vibrations and siloxane terminating vibrations, while the FESEM spectrum of EDX analysis corroborated the presence of silicon in OPF-SiO2. Likewise, the XRD diffractograms displayed prominent peaks at 2θ = 24°, indicating a predominantly amorphous silica structure. The XRF analysis further corroborated this result, which revealed that silica constituted 78 of the major elemental composition. The established optimized condition of D-µ-SPE extraction of PAHs required 60 mg of sorbent, an extraction time of 15 min using acetonitrile as the elution solvent, and a 5 min desorption time. The prepared sorbents exhibited a high affinity for PAHs through van der Waals and hydrogen bonding. The D-µ-SPE was linear between 50 and 5000 µg kg−1 for naphthalene, fluorene, anthracene, and pyrene (R2 = 0.9921–––0.9997). The RSDs were acceptable for intraday (0.65–1.52 , n = 3) and interday (0.60–1.92 ) analyses, coupled with low detection limits (2.33–4.90 µg kg−1) and satisfactory relative recovery (95.05–108.88 ). The experimental results supported the subsequent forcefield theory calculations for the PAHs and the OPF-SiO2 composite's interactions. Analytical GREEnness (AGREE) with a metric score 0.60 indicates that the developed approach is green.